2003
DOI: 10.1097/00004728-200301000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging for the Evaluation of Diffuse Axonal Injury in Closed Head Injury

Abstract: DWI is valuable in closed head injury because it identifies additional shearing injuries not visible on T2/FLAIR or T2* sequences. Furthermore, DWI/ADC maps differentiate between lesions with decreased or increased diffusion. DWI is less sensitive than T2* imaging for detecting hemorrhagic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(137 citation statements)
references
References 19 publications
1
127
1
8
Order By: Relevance
“…The typical diffusion times used for clinical DWI are 10 -50 ms, corresponding to average molecular displacements on the order of 10 m. This microscopic spatial scale is in the same range as that of cellular dimensions. This sensitivity to cellular processes has been exploited clinically for improving the detection of acute cerebral ischemia, 4,6-10 distinguishing vasogenic from cytotoxic edema, [11][12][13][14][15][16] identifying foci of axonal shearing injury after acute head trauma, [17][18][19] characterizing cellularity in brain tumors, [20][21][22][23][24][25][26][27] discriminating between metastases and gliomas 22,27 and between tumor recurrence and postsurgical injury, 28 differentiating pyogenic abscesses from tumors, [29][30][31] and for the noninvasive mapping of white matter connectivity by using the diffusion tensor model, [32][33][34][35][36] among other applications.…”
Section: Theoretic Underpinnings Of Diffusion Imagingmentioning
confidence: 99%
“…The typical diffusion times used for clinical DWI are 10 -50 ms, corresponding to average molecular displacements on the order of 10 m. This microscopic spatial scale is in the same range as that of cellular dimensions. This sensitivity to cellular processes has been exploited clinically for improving the detection of acute cerebral ischemia, 4,6-10 distinguishing vasogenic from cytotoxic edema, [11][12][13][14][15][16] identifying foci of axonal shearing injury after acute head trauma, [17][18][19] characterizing cellularity in brain tumors, [20][21][22][23][24][25][26][27] discriminating between metastases and gliomas 22,27 and between tumor recurrence and postsurgical injury, 28 differentiating pyogenic abscesses from tumors, [29][30][31] and for the noninvasive mapping of white matter connectivity by using the diffusion tensor model, [32][33][34][35][36] among other applications.…”
Section: Theoretic Underpinnings Of Diffusion Imagingmentioning
confidence: 99%
“…4,7,28 Light microscopic studies have shown that the density of thin diameter fibers reach a minimum and large myelinated fibers reach a maximum in the posterior truncus. 29,30 Increased ADC values could result from loss of myelin sheaths, a phenomenon that neuropathological review examinations have found to continue for 1-2 years post-injury.…”
Section: Neuropathological Origin Of Increased Adc Values In Differenmentioning
confidence: 99%
“…The application of diffusion weighted imaging (DWI) or diffusion tensor imaging (DTI) has yielded increased sensitivity in the detection of TAI. 2,7 DWI is based on the random movements of water molecules in the tissue known as ''Brownian motions.'' The rate of net diffusion of molecules is referred to as the ''apparent diffusion coefficient'' (ADC) value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractional anisotropy (FA) is sensitive to changes in white matter integrity (Watts et al, 2003). FA loss and D av rise have been demonstrated in a number of traumatic brain injury (TBI) studies (Huisman et al 2004;Lee, et al, 2003;Huisman et al 2003;Arfanakis, 2002). It is reasonable to assume that these quantitative characteristics are indicative of white matter damage in a variety of pathologies.…”
Section: Introductionmentioning
confidence: 99%